Reducing voltage sags through fault current limitation. - Tosato, F. (IEEE Transactions on power delivery)
Short circuit current limitation in distribution utilities can be an effective way to improve power quality, since the expected voltage sag amplitude during faults can be dramatically reduced. A simple series LC circuit tuned at the net frequency, with the capacitor shunted by a metal oxide varistor (MOV), proves to be a well suited limiter to reach the goal. In the paper, the properties of such a circuit are analyzed and its operation is investigated through computer simulation. The relevant pro and con aspects are outlined and discussed